1992
DOI: 10.1073/pnas.89.9.3889
|View full text |Cite
|
Sign up to set email alerts
|

Ras proteins are essential and selective for the action of insulin-like growth factor 1 late in the G1 phase of the cell cycle in BALB/c murine fibroblasts.

Abstract: BALB/c 3T3 cells (A31 cells) require the sequential action of growth factors in order to proliferate from a quiescent growth state. Insulin-like growth factor I (IGF-I) is needed late in the GI phase of the cell cycle, a time at which expression of the c-Ha-ras protooncogene is near maximal. An anti-ras antibody, introduced by microihjection, specifically blocked the ability of IGF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…Both c-Src and c-Ras have been implicated as cellular effectors of activated growth factor receptors, including the receptors for PDGF (24,42) and EGF (8,31). Indeed, Src may play a role in exit from G 0 and completion of G 1 (56), and Ras is thought to be necessary for the traverse of G 1 in BALB/c-3T3 cells (30). By contrast with their cellular proto-oncogene counterparts, v-src and v-ras encode mutant proteins that deliver constitutive mitogenic signals, even in the absence of growth factor receptor activation.…”
Section: Resultsmentioning
confidence: 99%
“…Both c-Src and c-Ras have been implicated as cellular effectors of activated growth factor receptors, including the receptors for PDGF (24,42) and EGF (8,31). Indeed, Src may play a role in exit from G 0 and completion of G 1 (56), and Ras is thought to be necessary for the traverse of G 1 in BALB/c-3T3 cells (30). By contrast with their cellular proto-oncogene counterparts, v-src and v-ras encode mutant proteins that deliver constitutive mitogenic signals, even in the absence of growth factor receptor activation.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of MAPK3/1 peaked from 15 to 30 min after the IGF1 stimulation. Earlier studies using fibroblasts indicated that RAS-MAP2K-MAPK3/1 activation is important in IGF1-related cell proliferation (Lu & Campisi 1992, Jhun et al 1994, Sasaoka et al 1996. In experiments using gynecological cancer cell lines, such as a cervical carcinoma cell line (SiHa) and an ovarian carcinoma cell line (OVCR3), IGF1 was reported to transmit the signal possibly via the MAPK3/1 pathway (Shen et al 2004).…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…Activation of both PI3K and MAPK pathways can induce proliferation in MCF7 cells (Lu & Campisi 1992, Jhun et al 1994, Dufourny et al 1997. As Lantus strongly phosphorylated and thus activated key signaling proteins of both pathways (Figs 2 and 3), we were interested in studying the role of either of the pathways in the proliferative ability of Lantus.…”
Section: Lantus Induced Proliferation In Mcf7 Cells Is Mainly Due To mentioning
confidence: 99%